y=2x-7 3y+2z=2 3x-4z=4和4x+9y=12 3y-2z=1 7x+5z=19/4三元一次方程帮写下解题过程(详细点)4x-9z=17 3x+y+15z=18 x+2y+3z=2和2x+4y+3z=9 3x-2y+5z=11 5x-6y+7z=13

来源:学生作业帮助网 编辑:作业帮 时间:2018/11/20 08:09:05
y=2x-73y+2z=23x-4z=4和4x+9y=123y-2z=17x+5z=19/4三元一次方程帮写下解题过程(详细点)4x-9z=173x+y+15z=18x+2y+3z=2和2x+4y+3

y=2x-7 3y+2z=2 3x-4z=4和4x+9y=12 3y-2z=1 7x+5z=19/4三元一次方程帮写下解题过程(详细点)4x-9z=17 3x+y+15z=18 x+2y+3z=2和2x+4y+3z=9 3x-2y+5z=11 5x-6y+7z=13
y=2x-7 3y+2z=2 3x-4z=4和4x+9y=12 3y-2z=1 7x+5z=19/4
三元一次方程帮写下解题过程(详细点)
4x-9z=17 3x+y+15z=18 x+2y+3z=2
和2x+4y+3z=9 3x-2y+5z=11 5x-6y+7z=13

y=2x-7 3y+2z=2 3x-4z=4和4x+9y=12 3y-2z=1 7x+5z=19/4三元一次方程帮写下解题过程(详细点)4x-9z=17 3x+y+15z=18 x+2y+3z=2和2x+4y+3z=9 3x-2y+5z=11 5x-6y+7z=13
y=2x-7 (1)
3y+2z=2 (2)
3x-4z=4 (3)
(2)*2+(3)得
3x+6y=8
将(1)式代入,消去y得
15x-42=8
解得x=10/3
由(1)式y=2*10/3-7=-1/3
由(2)式z=1/2*(3y-2)=-3/2
4x+9y=12 (1)
3y-2z=1 (2)
7x+5z=19/4 (3)
(1)-(2)*3得
4x-6z=9 (4)
(3)*4-(4)*7,消去y得
62z=-44解得z=-22/31
由(4)式x=1/4*(9+6z)=147/124
由(2)式y=1/3*(1+2z)=-13/93
4x-9z=17 (1)
3x+y+15z=18(2)
x+2y+3z=2 (3)
(2)*2-(3)得
5x+27z=34 (4)
(1)*3+(4)得
17x=85
解得x=5
由(1)得z=1/9*(4x-17)=1/3
又(2)得 y=18-3x-15z=18-15-5=-2
2x+4y+3z=9 (1)
3x-2y+5z=11 (2)
5x-6y+7z=13 (3)
(1)+(2)*2得
8x+13z=31 (4)
(2)*3-(3)得
4x+8z=26 (5)
(5)*2-(4)得
3z=21解得
z=7
由(5)得 x=1/4*(26-8z)=-15/2
由(1)得 y=1/4*(9-2x-3z)=9/2

第一题:Y=2X-7 (1)

3Y+2Z=2 (2)
3X-4Z=4 (3)
解:将(1)代入(2)得:
3(2X-7)+2Z=2
6X+2Z=23 (4)
(3)+(4...

全部展开

第一题:Y=2X-7 (1)

3Y+2Z=2 (2)
3X-4Z=4 (3)
解:将(1)代入(2)得:
3(2X-7)+2Z=2
6X+2Z=23 (4)
(3)+(4)×2得:
15X=50 解之 得:X=10/3
把X=10/3代入到(3)得:
3×10/3-4Z=4
解之得:Z=3/2
再把X=10/3代入到(1)得:
Y=2×10/3-7=-1/3
所以 X=10/3 Y=-1/3 Z=3/2 ;

第二题: 4X+9Y=12 (1)
3Y-2Z=1 (2)
7X+5Z=19/4 (3)
(1)-(2)×3 得
4X+6Z=9 (4)
(3)×6-(4)×5 得
22X=-33/2
X=-3/4
把X=-3/4代入到(4)得
Z=2
把Z=2代入到(2)得
Y=5/3
所以 X=-3/4;Y=5/3;Z=2;

收起